1984
DOI: 10.1677/joe.0.1010305
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic GMP phosphodiesterase and guanylate cyclase activities in rabbit ovaries and the effect of in-vivo stimulation with LH

Abstract: The activities of guanylate cyclase and cyclic GMP (cGMP) phosphodiesterase, enzymes that are responsible for maintaining tissue levels of cGMP, were determined in the ovaries of rabbits killed without treatment or 4 h after administration of LH. Ovarian activities of the two enzymes were determined in the 100 000 g supernatant fraction (cytosol) and the resulting pellet (particulate fraction). Significant phosphodiesterase and cyclase activities were detected in both the cytosol and particulate fractions. Adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
5
11
0
Order By: Relevance
“…The decrease in cGMP in the follicle does not appear to be associated with follicular activation of cGMP-PDEs, as we were unable to detect increased activity of these enzymes over a period of 2 h of LH stimulation (data not shown), consistent with a previous study [42] in the rabbit. Results of another study [43] have shown that gonadotropins do not affect cGMP hydrolysis in cultured granulosa cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The decrease in cGMP in the follicle does not appear to be associated with follicular activation of cGMP-PDEs, as we were unable to detect increased activity of these enzymes over a period of 2 h of LH stimulation (data not shown), consistent with a previous study [42] in the rabbit. Results of another study [43] have shown that gonadotropins do not affect cGMP hydrolysis in cultured granulosa cells.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, LH still causes a decrease in cGMP in the presence of PDE5 inhibitors, further excluding the possibility that LH acts through activation of a cGMP-PDE. In several species, LH modulates NO production [23,44,45], which may in turn modulate guanylate cyclase activity [42]. Therefore, it is possible that the mechanism by which LH regulates cGMP in the mouse POF is via the NO-guanylate cyclase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in cGMP in the somatic cells could result from inhibition of a guanylyl cyclase or from stimulation of a cGMP phosphodiesterase. There is some evidence for regulation of the cyclase rather than the phosphodiesterase (Patwardhan and Lanthier, 1984), although it remains to be determined which particular guanylyl cyclases and/or phosphodiesterases are involved, how they are regulated, and whether interfering with LH-induced changes in their activity prevents meiotic resumption. It is also unknown whether EGF receptor activation functions in the pathway by which LH causes cGMP levels to decrease in the somatic cells.…”
Section: Monitoring Camp and Cgmp Levels In Intact Follicle-enclosed mentioning
confidence: 99%
“…The increased activity of cGMP-PDEs is unable to be detected during LH stimulation [19,101], and gonadotropins do not affect cGMP hydrolysis in cultured granulosa cells [102]. Furthermore, LH still causes a decrease in cGMP in the presence of cGMP special PDE5 inhibitors [19].…”
Section: Lh-induced Meiotic Resumptionmentioning
confidence: 99%
“…These results exclude the possibility that LH acts through activation of a cGMP-PDE. There is some evidence for regulation of the cyclase rather than the phosphodiesterase [101]. It is interesting that Nppc and Npr2 mRNA levels, and NPPC peptide levels are decreased in mouse follicle cells and human follicular fluid after treated by human chorionic gonadotropin (hCG), a pregnancy hormone that exhibits LH activity with a long serum half-life ( [71,103], and data not shown), which could decrease cGMP levels in the follicle cells.…”
Section: Lh-induced Meiotic Resumptionmentioning
confidence: 99%